Studi Kritis Pemikiran Politik Ali Abdul Raziq - Agung Prawoto (Universitas Darussalam Gontor, 2018)
This paper examines the political thought of Ali Abdul Raziq, a Egyptian Muslim figure. ‎His political idea convinces a controversy between Muslim and Western scholars. Back In his ‎country, he is opposed by a number of Muslim scholars because his thought bothered some parties. His idea, particularly arguing that that politic and religion are indeed two different ‎things; politic is substantially khila>fah, qada’ and governmental ‎task matters which derived from mundane perspectives, while religion, in the other hands underlies merely the issue of Muslim faith. His thought is highly appreciated by Westerners ‎and even considered as a crucial progress of politic in Islam. Antony ‎Black, for instance. He praised Ali as the revolutionist. In spite of it, it is crucial for readers to realize that the ‎essence of argument given by Ali is anemic and contrast to Islam. Therefore, it is a need to examine Ali’s political discussion with further empirical evidences. After examining his work, researcher finds at least there are four fundamental arguments influencing his thought. First, ‎the absence of hujjah syar’iyyah that upholds the concept imamate. Second, the concept of khila>fah is not ‎required by Muslims. Third, the treatise accomplished by Prophet Muhammad is purely ‎based on religious aspect. And the last, politic is an independent concept that should be ‎drifted apart from religious elements. Consequently, Ali’s bias toward secularism is clear; particularly in his approval separating state from any religion institutions. This assumption is also ‎built up by the fact that he was a student of two orientalists, Mallino and Sentillana, who taught him during his study at the University of Egypt (al-Ja>mi’ah al-Misriyyah).